The three faces of a digital attack: an analysis of cyber-crime, cyber-terrorism and hacktivism (The Journal of Forensic Accounting Profession, 2026)
In the modern digital age, the boundaries between crime, terrorism and hacktivism in cyber space are becoming increasingly blurred. Although the usual elements of violence, political motivation, threat and fear provide a line of continuity that runs through the long and complex history of terrorism, it should also be taken into account that technological innovation has created a new form of terrorism. In recent years, the matter of “cyber” terrorism has become very interesting, as a kind of form of computer crime. Cyber terrorism implies the use of information resources in the form of threats or blackmail in order to achieve a specific terrorist goal. In the focus of attention is the abuse of the Internet as the most important global communication network. The use of the Internet by terrorists can be threefold: as a weapon, as a means of communication between activists and as a medium for addressing the public. Precisely for these reasons, it is necessary to spread the culture of using computer technology, but attention should also be paid to the security culture. After an unsuccessful defense against a cyber attack, Internet forensics allows us to reconstruct the events in order to discover the attackers and their methods of operation. Given that it is an extremely complex matter, in the paper we also looked at the general determinants related to computer crime, computer terrorism and hacktivism.(Previously published on Sciendo: https://reference-global.com/article/10.2478/jfap-2025-0010, under licence CC BY-NC-ND 4.0)
Keywords: cyber crime; cyber terrorism; terrorism; criminality; information and communication technology